The Thermoelastic Dynamic Response of Thick Closed Laminated Shell - Ke Wei Ding (Shock and Vibration)
Giving up any assumptions about displacement models and stress distribution, weak formulation of mixed state equations including boundary conditions of laminated cylindrical shell are presented. Thermal stresses mixed Hamilton equation of closed cylindrical shell is established. The analytical solutions are obtained for the thermoelastic dynamic response of a thick closed laminated shell subjected to temperature variation. Every equation of elasticity can be satisfied, and all elastic constants can be taken into account. Arbitrary precision of a desired order can be obtained.